ANALISIS PELAKSANAAN PEMBAYARAN ROYALTI HAK CIPTA LAGU TERHADAP PELAKU USAHA HIBURAN KARAOKE (Studi Kasus Orange family Karaoke) - suci permata; Tami Rusli; Melisa Safitri (Fakultas Hukum Universitas Tulang Bawang, 2021)
Abstract Karaoke places are in great demand from various circles. All karaoke places have the same goal, which is to provide entertainment for the family or take a moment to unwind from the daily routine. Karaoke places always serve songs with various choices from all the creations of Indonesian singers. But of course the songs that are served have been licensed first. Regarding this license, basically it must be agreed by both parties without coercion. Copyright protection, especially for music or song creations, is a serious problem. This situation shows that there is still a need for stricter legal protection regarding the protection of royalties on a song or music copyrighted work and the protection of the rights contained therein. The purpose of the study was to determine the implementation of copyright royalty payments on songs between the creator and karaoke entertainment business actors and the inhibiting factors for the payment of copyright royalties on songs between the creator and performer in karaoke entertainment at Orange Family Karaoke. The method used in this research is empirical juridical. The data that has been systematically arranged were analyzed qualitatively. The results showed that the distribution of royalties is managed by the Collective Management Institute (LMK). The institution is authorized by the creator to exercise the economic rights of the creator. The barrier to royalty payments is due to the lack of socialization and understanding of royalty payments and the high cost of royalty payments. Â Keywords: Royalty, Copyright, Karaoke